Hubungan Penguasaan Teori Pemasangan Instalasi Penerangan Listrik Berbantuan Modul Dengan Kompetensi Praktik Siswa di SMK Negeri 1 Pariaman - Yosi Lolita Sari; Elfizon Elfizon (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
This study aimed to look at the relationship between the mastery of the theory of the installation of the module-assisted electric lighting installation with the practice competencies of the XI TITL students in SMK Negeri 1 Pariaman. Learning to install electric lighting (IPL) is still not optimal because there are still many students asking for the material to be done. Therefore it is necessary to research the relationship of mastery of theory assisted modules with student practice competencies. This type of research uses correlational study methods. Correlational research is research used to see the relationship between one variable with another variable. From the results of normality testing data processing, the significance value of variable x (mastery of theory) = 0.664> alpha = 0.05 and the significance value of variable y (practice competency) = 0.794> alpha = 0.05, so the data is said to be normally distributed. For the linearity test, the significance value of deviation from linearity is obtained = 0.221> 0.05, so that the variables x and y are said to be linear. Hypothesis testing obtained the correlation coefficient value of 0.767. The price of rtable n 20 = 0.444 with a significant level of 5% so the price of rcount> rtable, meaning that there is a relationship between the mastery of the theory of the installation of electrical aids assisted in modules with the practical competence of students in class XI TITL at SMK Negeri 1 Pariaman.